Consumption and uncertain access to the asset market - Leena Rudanko (Bank of Finland, 2000)
This paper presents a new approach to modelling credit restrictions by considering uncertain access to the asset market.The asset market and the stochastic process governing access are considered fully exogenous and independent of income.The model generates stable debt trajectories for a broader array of interest rate levels than the one corresponding to the agent's rate of time preference.The agent exhibits excess sensitivity of consumption to current period income, even for low probabilities of constraints. Because this sensitivity is inversely related to the maturity of debt contracts, the availability of long-term debt contracts reduces the income-sensitivity of consumption.A very tractable approximative Euler equation for the model is presented.
URN:NBN:fi:bof-20140807190
Keywords: 330